P18 Integrating simulation-based education and precision teaching to improve physicians' performance of lumbar puncture in clinical practice. (3rd November 2019) - Reid-McDermott, Bronwyn; Lydon, Sinéad; O'Connor, Paul; Bhulbh, Áine de; Hanahoe, Belinda; Byrne, Dara
Abstract : Background: Lumbar puncture (LP) for cerebrospinal fluid (CSF) is an invasive procedure used for diagnosis and treatment and is performed by doctors of various specialties. Unsuccessful LPs can result in adverse patient outcomes such as prolonged pain and immobilisation; while traumatic LPs can complicate the interpretation of CSF white cell counts, render the tap non-diagnostic and necessitate additional testing. Rates of unsuccessful and 'traumatic taps' can be as high as 30%. 1 Simulation technology may provide an approach to improving the competency of doctors in this task. This study aimed to describe the application of precision teaching (PT), an instructional methodology used to produce behavioural fluency, to simulation-based skills training. Behavioural fluency refers to accurate and speedy responding that does not deteriorate with time, is resistant to distraction, and persists in novel contexts. Summary of work: A Randomised controlled trial was conducted with senior house officers in a large teaching hospital. The intervention group (n=10) received fluency training targeting the performance of LP. A control group (n=11) received training as usual. The performance of the two groups at baseline and post-test will be compared. Further post-intervention evaluations will be conducted to assess skill retention, stability and transference to the clinical environment. Laboratory data will be assessed in order to compare rates of 'bloody taps' in LPs conducted in hospital settings among trained and untrained doctors. Summary of results: This study is ongoing. To date, three participants have achieved fluency, requiring an average of six trials on the LP simulator and 132 minutes of fluency training to reach the pre-defined fluency criterion for the LP skill. Stability trials have been completed by two of the fluent participants. Both trials demonstrated that fluency remained stable in the presence of distraction. Discussion, conclusions and recommendations: Combining simulation-based education and PT to establish behavioural fluency in procedural skills could minimise the potential risk to patients and ensure that learners receive training and feedback in an individualised yet systematic way. Analysing the number of bloody taps in the trained versus an untrained group of their peers to look for translation of the teaching to clinical practice is a good measure of the effect of this type of training on patient outcomes and of return on investment. References: Gottlieb M, Holladay D, Peksa GD. Ultrasound-assisted Lumbar Punctures: A Systematic Review and Meta-Analysis. Academic Emergency Medicine . 2019 Jan;26(1):85–96.